Forecasting the incidence of dengue in Bangladesh—Application of time series model. Issue 4 (8th June 2022) - Naher, Shabnam; Rabbi, Fazle; Hossain, Md. Moyazzem; Banik, Rajon; Pervez, Sabbir; Boitchi, Anika Bushra
Abstract: Background: Dengue is an alarming public health concern in terms of its preventive and curative measures among people in Bangladesh; moreover, its sudden outbreak created a lot of suffering among people in 2018. Considering the greater burden of disease in larger epidemic years and the difficulty in understanding current and future needs, it is highly needed to address early warning systems to control epidemics from the earliest. Objective: The study objective was to select the most appropriate model for dengue incidence and using the selected model, the authors forecast the future dengue outbreak in Bangladesh. Methods and Materials: This study considered a secondary data set of monthly dengue occurrences over the period of January 2008 to January 2020. Initially, the authors found the suitable model from Autoregressive Integrated Moving Average (ARIMA), Error, Trend, Seasonal (ETS) and Trigonometric seasonality, Box‐Cox transformation, ARMA errors, Trend and Seasonal (TBATS) models with the help of selected model selection criteria and finally employing the selected model make forecasting of dengue incidences in Bangladesh. Results: Among ARIMA, ETS, and TBATS models, the ARIMA model performs better than others. The Box‐Jenkin's procedure is applicable here and it is found that the best‐selected model to forecast the dengue outbreak in the context of Bangladesh is ARIMA (2, 1, 2). Conclusion: Before establishing a comprehensive plan for future combating strategies, it is vital to understand the future scenario of dengue occurrence. With this in mind, the authors aimed to select an appropriate model that might predict dengue fever outbreaks in Bangladesh. The findings revealed that dengue fever is expected to become more frequent in the future. The authors believe that the study findings will be helpful to take early initiatives to combat future dengue outbreaks.